Green synthesis and characterization of Mg0.93Na0.07O nanoparticles for antimicrobial activity, cytotoxicity and magnetic hyperthermia. Issue 19 (1st October 2022) - Bhoi, Himani; Tiwari, Sudeep; Lal, Ganesh; Jani, Komal K.; Modi, Shrey K.; Seal, Papori; Saharan, Vinod; Modi, Kunal B.; Borah, J.P.; Punia, Khushboo; Kumar, Sudhish
Abstract: We have investigated structural, optical, magnetic, magnetic induction heating, cytotoxicity and antimicrobial properties of 7% Na doped MgO nanoparticles (Mg0.93 Na0.07 O NPs) synthesized by green self-combustion route using fresh lemon juice as capping and reducing agent. PXRD, FESEM, FEG-TEM, SAED, FTIR and PL analysis confirmed formation of highly crystalline single-phase, ∼26(±5)nm sized Mg0.93 Na0.07 O NPs in the NaCl type fcc structure. AFM measurements showed agglomeration of grains. Diffuse reflectance analysis demonstrated maximum reflectance change in the UV & blue color region and wide bandgap of ∼4.79eV for Mg0.93 Na0.07 O NPs. 240 nm excited PL emission data exhibited broad emission centered at ∼389 nm and oxygen vacancies in the MgO lattice. ESR study also revealed presence of F-center type defects in the MgO lattice.VSM measurements established superparamagnetic character of Mg0.93 Na0.07 O NPs along with some signature of d 0 type soft ferromagnetic ordering at RT, which can be well understood in BMP model. Heat generation efficiency of Mg0.93 Na0.07 O NPs (SAR = 123.5 W/g) is suitable for mild hyperthermia cancer therapy. Mg0.93 Na0.07 O NPs showed remarkable antibacterial and antifungal activity against few common pathogens. MIC values of Mg0.93 Na0.07 O NPs against gram-positive S. aureus & S. pyogenes, gram negative E. coli bacteria and C. albicans fungi were found to be comparable to standard drugs. In vitro cytotoxicity of Mg0.93 Na0.07 O NPs has been tested on normal fibroblast cells and MCF-7 breast cancer cells by MTT assay method, which showed dose dependent response. Findings revealed that cancer cell viability significantly decreases with increasing concentration of Mg0.93 Na0.07 O NPs, however these nanoparticles also showed considerable toxic effect on normal cells at higher concentration. Antimicrobial activity and cytotoxicity of Mg0.93 Na0.07 O NPs is attributed to generation of ROS on the surface of nanoparticles. This study demonstrates that greenly synthesized Mg0.93 Na0.07 O NPs might be suitable for food packaging, bactericide for water purification and biomedical applications. Graphical abstract: Image 1 Highlights: Na doped MgO NPs were obtained by green self-combustion synthesis route using fresh lemon juice. Na doped MgO NPs display superparamagnetism with some signature of d 0 type soft ferromagnetic ordering at RT. The heat generation efficiency of Mg0.93 Na0.07 O NPs (SAR = 123.5 W/g) is suitable for mild hyperthermia cancer therapy. MIC values of Mg0.93 Na0.07 O against gram-positive S. aureus & S. pyogenes and gram negative E. coli bacteria are comparable to standard drugs. Mg0.93 Na0.07 O NPs exhibit strong antifungal activity against C. albicans fungi. In vitro cytotoxicity of Mg0.93 Na0.07 O NPs has been tested on normal fibroblast cells and MCF-7 breast cancer cells by MTT assay method, which showed dose dependent response.